\[\boxed{\mathbf{811\ (811).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ y = x² - 4x + 4\]
\[y = (x - 2)^{2}\]
\[Сдвигаем\ y = x^{2}на\ 2\ единицы\ \]
\[вправо.\]
\[\text{E\ }(y) = \lbrack 0; + \infty);\ \ \]
\[убывает\ на\ ( - \infty;\ 2\rbrack;\ \ \]
\[возрастает\ \lbrack 2; + \infty).\]
\[2)\ y = 2x² + 8x + 8\ \]
\[y = 2 \cdot \left( x^{2} + 4x + 4 \right)\]
\[y = 2 \cdot (x + 2)^{2}\]
\[Сдвигаем\ y = 2x^{2}\ на\ \]
\[\ 2\ единицы\ влево.\]
\[E(y) = \lbrack 0;\ + \infty);\]
\[\ убывает\ \ ( - \infty; - 2\rbrack;\ \ \]
\[возрастает\ \lbrack - 2;\ + \infty).\]
\[\boxed{\mathbf{811.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[1)\ 2x² + ax + a - 2 = 0\]
\[D = a^{2} - 8 \cdot (a - 2) =\]
\[= a^{2} - 8a + 16 = (a - 4)^{2}\]
\[(a - 4)^{2} > 0\ \ \ \ при\ всех\ \ a \neq 4.\]
\[Ответ:при\ a \neq 4.\]
\[2)\ (2a - 1)x² + (a - 3)x + 1 = 0\]
\[D = (a - 3)^{2} - 4 \cdot (2a - 1) =\]
\[= a^{2} - 6a + 9 - 8a + 4 =\]
\[= a^{2} - 14a + 13 =\]
\[= (a - 13)(a - 1)\]
\[\left\{ \begin{matrix} (a - 13)(a - 1) > 0 \\ 2a - 1 \neq 0\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \\ \end{matrix} \right.\ \text{\ \ \ \ \ \ \ \ }\]
\[\ \left\{ \begin{matrix} (a - 13)(a - 1) > 0 \\ a \neq \frac{1}{2}\text{\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ } \\ \end{matrix} \right.\ \]
\[Ответ:при\ a( - \infty;0,5) \cup\]
\[\cup (0,5;1) \cup (13;\ + \infty).\]
\[3)\ ax² - (3a + 1)x + a = 0\]
\[D = (3a + 1)^{2} - 4a^{2} = 9a^{2} +\]
\[+ 6a + 1 - 4a^{2} = 5a^{2} + 6a +\]
\[+ 1 > 0,\ \ a \neq 0\]
\[5a^{2} + 6a + 1 = 0\]
\[D = 36 - 20 = 16\]
\[a = \frac{- 6 + 4}{10} = - \frac{1}{5},\]
\[\ \ a = \frac{- 6 - 4}{10} = - 1\]
\[Ответ:при\ a \in ( - \infty;\ - 1) \cup\]
\[\cup ( - 0,2;0) \cup (0;\ + \infty).\]